ASSESSMENT OF HYGIENIC PRACTICES OF SELECTED “LECHONEROS” AND MICROBIOLOGICAL QUALITY EVALUATION OF PORK “LECHON” IN A LOCALITY OF LEYTE, PHILIPPINES - Cagabhion, Anastacio T; Alo, Omar D; Licatan, Marjorie A; Looc, Cerela S; Emnace, Ivy C (Journal of Agriculture and Technology Management, 2021)
Originally introduced as a Spanish pork dish, the “lechon” refers to a pig that is slow roasted. It is a well- liked cuisine that is always present during festivities. Since “lechon” is one of the most favorite dishes and is now being sold in retail (kilos), it is appropriate to highly consider its quality. This study aimed to assess the practices employed in the production and distribution of “lechon” and evaluate the microbial quality of the “lechon” sold in the retail market in a locality in Leyte, Philippines. Four randomly selected “lechoneros” were interviewed and actual assessment of the processing area and hygienic practices were done. Aerobic plate count on the raw and cooked “lechon” was conducted. Results showed that only one out of the four “lechoneros” would subject the animal to the slaughterhouse for slaughtering. Three out of the four “lechoneros” were non-compliant on the ante-mortem and post-mortem inspection of the pigs. Mean microbial load for dorsal, ventral, rostral and caudal areas of raw meat are 8.13x10 6 ,  3.75x10 6 ,  4.15x10 7 ,  3.13x10 7   CFU/g, respectively. Mean microbial load for cooked meat is 1.82x10 8 CFU/g. Furthermore, the microbial load for the raw and cooked meat samples failed to meet the standards of the good manufacturing practice and microbiological standards for food which are 10 5 and 10 6 , respectively.